C0G microwave dielectric material with medium dielectric constant and high Q value and preparation method thereof

By combining BaTi4O9 and BaSm2Ti4O12 and doping modifiers, C0G microwave dielectric material with a dielectric constant ranging from 50 to 60 and having a high Q*f value and a low dielectric loss was prepared, and the dielectric constant in the prior art was solved The problem of inconsistent with Q value is applicable to the field of microwave mobile communications.

CN119462127APending Publication Date: 2025-02-18CHENGDU HONGMING & UESTC NEW MATERIALS
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411347935.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The prior art lacks microwave dielectric materials with dielectric constants between 50 and 60 and high Q value, which limits its wide application in the field of microwave mobile communications.

Method used

By combining BaTi4O9 and BaSm2Ti4O12, (1-x)BaTi4O9-xBaSm2Ti4O12 is formed as the main crystal phase, and MnCO3, Bi2O3, CeO2, BaTiO3, SrTiO3 and SrTiO3 are doped as modifiers, combined with CaO-B2O3-SiO2 glass, the dielectric constant and Q*f value.

Benefits of technology

A microwave dielectric material with a dielectric constant in the range of 50 to 60, a dielectric loss <2.5×10-4, a capacity temperature coefficient <±30ppm/℃, Q*f>20000, and a C0G characteristic, satisfies microwave mobile communication miniaturized design requirements and low loss requirements in the field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119462127A_ABST
    Figure CN119462127A_ABST
Patent Text Reader

Abstract

The invention discloses a C0G microwave dielectric material with a medium dielectric constant and a high Q value and a preparation method of the C0G microwave dielectric material, and relates to the technical field of microwave dielectric materials. The material is composed of a main crystalline phase material, a first modifier, a second modifier and glass. The main crystal phase material is (1-x) BaTi < 4 > O < 9-x > BaSm < 2 > Ti < 4 > O < 12 >, and x is more than or equal to 0.1 and less than 0.2; the first modifier is one or more of MnCO3 (manganese carbonate), Bi2O3 (bismuth oxide) and CeO2 (cerium oxide); the second modifier is one or more of BaTiO3 (barium titanate) and SrTiO3 (strontium titanate); the microwave dielectric material prepared by the invention has a dielectric constant of 50-60, a high dielectric constant, low dielectric loss and a high Q * f value, and has a C0G characteristic.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of microwave dielectric materials, and in particular to a COG microwave dielectric material with a high dielectric constant Q value and a preparation method thereof. Background Art

[0002] With the continuous development of microwave mobile communications, the research and application of microwave dielectric materials has become a hot research direction in the field of domestic materials. Microwave dielectric materials are mainly used to make resonators, filters, dielectric substrates, dielectric antennas, etc., and are widely used in mobile phones, TV satellite receivers, satellite broadcasting, radar and other military and civilian fields.

[0003] Microwave dielectric materials are mainly divided into three categories: low dielectric constant (<20), medium dielectric constant (20<ε<70), and high dielectric constant (>70). Among them, microwave dielectric materials with low dielectric constant are the earliest microwave dielectric materials, with very high Q*f values, and are mainly used in microwave substrates and high-end microwave components; microwave dielectric materials with medium dielectric constant are mainly used in satellite communications and mobile base stations, and their Q*f values ​​are relatively high; microwave dielectric materials with high dielectric constant can greatly reduce the product size of microwave devices, but the higher the dielectric constant, the better. Too high a dielectric constant will affect the transmission loss. The appropriate dielectric constant and higher Q*f value can not only meet the needs of miniaturization design, but also reduce the filter's incorporation loss, making the filter have better filtering function. Therefore, microwave dielectric materials with medium dielectric constant are widely used in the field of microwave mobile communications.

[0004] Intermediate microwave dielectric materials with a dielectric constant of 20 to 70 are mainly used as dielectric resonant devices in microwave military radars and microwave communication systems. The miniaturization of mobile communication base stations urgently requires the research and development of new microwave dielectric ceramic materials with high Q values ​​(Q*f values>20000GHz) and medium εr with small frequency temperature coefficients. At present, in the research on intermediate microwave dielectric ceramics, most of them are concentrated on dielectric constants of 20 to 50, and there is little research on dielectric constants between 50 and 60. There is also a lack of microwave dielectric materials with dielectric constants between 50 and 60 and high Q*f values ​​on the market. Among the microwave dielectric materials with dielectric constants of 50 to 60 disclosed in CN106045513A, the SrO-CaO-MgO-ZnO-TiO2-Ta2O5 system is used, and the Ta2O5 content is as high as 63% to 73%, which is relatively costly and limits its promotion and application. Summary of the invention

[0005] The present invention aims to solve the technical problem that the prior art lacks microwave dielectric materials with a dielectric constant of 50 to 60 and a high Q value, and aims to provide a C0G microwave dielectric material with a dielectric constant and a high Q value and a preparation method thereof, so as to obtain a C0G microwave dielectric material with a dielectric constant of 50 to 60 and a dielectric loss of less than 2.5×10 -4 , capacity temperature coefficient <±30ppm / ℃, Q*f>20000, and microwave dielectric material with C0G characteristics.

[0006] The present invention is achieved through the following technical solutions:

[0007] The first object of the present invention is to provide a COG microwave dielectric material with a dielectric constant and a high Q value, the composition of which is composed of a main crystal phase material, a first modifier, a second modifier and glass;

[0008] The main crystalline phase material is (1-x)BaTi4O9-xBaSm2Ti4O 12 , where 0.1≤x<0.2;

[0009] The first modifier is one or more of MnCO3, Bi2O3, and CeO2;

[0010] The second modifier is one or more of BaTiO3 and SrTiO3;

[0011] The glass is CaO-B2O3-SiO2 glass.

[0012] Furthermore, the weight percentage of each component of the COG microwave dielectric material is:

[0013] 0wt%~0.7wt%MnCO3, 0wt%~0.75wt%Bi2O3, 0wt%~0.6wt%CeO2, 0wt%~3wt%SrTiO3, 0wt%~1.5wt%BaTiO3, 0wt%~0.5wt%CaO-B2O3-SiO2 glass, the balance is mainly crystalline material (1-x)BaTi4O9-xBaSm2Ti4O 12 .

[0014] Furthermore, the weight percentage of each component of the COG microwave dielectric material is:

[0015] 0.1wt% MnCO3, 0.1wt% CeO2, 0.5wt% SrTiO3, 0.1wt% CaO-B2O3-SiO2 glass and the remainder of the main crystalline phase material, wherein the main crystalline phase material is 0.82BaTi4O9-0.18BaSm2Ti4O 12 .

[0016] Furthermore, the composition of the CaO-B2O3-SiO2 glass is:

[0017] 38wt% ~ 45wt% CaCO3, 17wt% ~ 25wt% B2O3, 30wt% ~ 45wt% SiO2.

[0018] The second object of the present invention is to provide a method for preparing a COG microwave dielectric material with a dielectric constant and a high Q value, comprising the following steps:

[0019] CaCO3, B2O3 and SiO2 are mixed according to the weight ratio, ball-milled for 5-7 hours, dried and sintered at 650±20℃ to form CaO-B2O3-SiO2 glass;

[0020] BaCO3, TiO2, Sm2O3 are used as raw materials, according to (1-x)BaTi4O9-xBaSm2Ti4O 12 The chemical formula ingredients are ball-milled for 8h to 12h, then dried, sieved, and gradually heated to 1200℃ for calcination to obtain the main sintered block material;

[0021] The main sintered block material, the first modifier, the second modifier and the CaO-B2O3-SiO2 glass are mixed in proportion, ball-milled for 20 to 26 hours, dried and sieved to obtain the porcelain material;

[0022] The ceramic material is granulated, pressed into discs, debonded, gradually heated to 1270±20° C., and sintered for 2 to 4 hours to obtain a C0G microwave dielectric material.

[0023] Furthermore, when preparing CaO-B2O3-SiO2 glass, alcohol is used as the medium and ball milling mixing is performed in a ratio of material: ball: alcohol = 1:5:1.

[0024] Furthermore, when preparing the main sintered block material, water is used as the medium and ball milling is performed in a ratio of material: ball: water = 1:3:2.

[0025] Furthermore, when preparing the porcelain material, water is used as the medium and ball milling and mixing are performed in a ratio of material: ball: water = 1:5:1.2.

[0026] Further, the ceramic material is granulated, pressed into discs, and debonded, including:

[0027] The porcelain material is added with 8-9 wt% paraffin wax to form granules, which are pressed into discs using a hydraulic press, and then heated to 450°C to discharge the adhesive.

[0028] Furthermore, the heating rate is 2-4°C / min.

[0029] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0030] 1. The present invention uses BaTi4O9 and BaSm2Ti4O 12 Composite, forming (1-x)BaTi4O9-xBaSm2Ti4O 12 As the main crystal phase, the main sintered block material has an adjustable dielectric constant, low dielectric loss, and high Q*f value, and the dielectric constant is in the range of 50 to 60, and the dielectric loss is less than 2.5×10 -4 , capacity temperature coefficient <±30ppm / ℃, Q*f>20000, and microwave dielectric material with C0G characteristics.

[0031] 2. In order to ensure that the material has a higher dielectric constant, low dielectric loss and a high Q*f value, the present invention refines the grains, reduces the internal defects of the porcelain body, and makes the material structure uniform by doping one or more of the first modifiers MnCO3, Bi2O3, and CeO2 to reduce dielectric loss. The second modifier is added with one or more of BaTiO3 and SrTiO3, and the temperature change rate of the capacity is adjusted by using substances with positive and negative change rates. The material has the characteristics of a higher dielectric constant, low dielectric loss and a high Q*f value.

[0032] 3. The present invention adds a small amount of glass, so that a liquid phase is first formed to wrap around the surface of the grains during the sintering process, which accelerates the migration of substances and the discharge of gases, reduces the porosity, and improves the density of the porcelain body.

[0033] 4. The raw materials in the present invention are all domestically produced, low-cost and sufficient in quantity. The preparation process of the porcelain material is simple, suitable for mass production, and has high promotion and application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, other relevant drawings can be obtained based on these drawings without creative work. In the drawings:

[0035] Figure 1 This is the SEM image of the ceramic material of formula 6;

[0036] Figure 2 This is the SEM image of the ceramic body after sintering of the ceramic material of formula 6;

[0037] Figure 3 These are the XRD diagrams of the porcelain bodies of Formula 1, Formula 4, Formula 6, and Formula 9. DETAILED DESCRIPTION

[0038] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the technical solutions in the embodiments of the present invention are clearly and completely described below in combination with the embodiments and drawings. Obviously, the schematic implementation modes of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.

[0039] The following is a detailed description of an embodiment of a COG microwave dielectric material with a dielectric constant and a high Q value and a preparation method of the present invention with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there may be cases where detailed descriptions and repeated descriptions of well-known matters are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art.

[0040] The "range" disclosed in this application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range.

[0041] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0042] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0043] Unless otherwise specified, the terms "include" and "comprising" mentioned in this application may be open-ended or closed-ended. For example, the terms "include" and "comprising" may mean that other substances not listed may also be included or only the listed substances may be included.

[0044] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0045] To achieve the purpose of the present invention, the technical solution of the present invention is to provide a C0G microwave dielectric material with a dielectric constant and a high Q value, wherein the composition of the material is composed of a main crystalline phase material, a first modifier, a second modifier and glass;

[0046] The main crystalline phase material is (1-x)BaTi4O9-xBaSm2Ti4O 12 , where 0.1≤x<0.2;

[0047] The first modifier is one or more of MnCO3, Bi2O3, and CeO2;

[0048] The second modifier is one or more of BaTiO3 and SrTiO3;

[0049] The glass is CaO-B2O3-SiO2 glass.

[0050] BaTi4O9 has excellent performance among BaO-TiO2 series microwave dielectric materials and is a typical representative of intermediate microwave dielectric ceramics. Its dielectric constant is about 38 and its dielectric loss is 5×10 -4 , Q*f can reach more than 30000, and the capacity temperature coefficient is about +50ppm / ℃, but its dielectric constant is difficult to reach 50. BaSm2Ti4O in the BaO-Ln2O3-TiO2 system 12 , the dielectric constant is greater than 80, the Q*f value can reach more than 8000GHz, and it has a low capacity temperature coefficient. Therefore, the present invention uses BaTi4O9 and BaSm2Ti4O 12 Composite, forming (1-x)BaTi4O9-xBaSm2Ti4O 12 As the main crystal phase, the main sintered block material has an adjustable dielectric constant, low dielectric loss, and a high Q*f value.

[0051] In order to ensure that the dielectric constant is high, the dielectric loss is low and the Q*f value is high, one or more of the first modifiers MnCO3, Bi2O3 and CeO2 are doped to refine the grains and reduce the internal defects of the porcelain body, thereby reducing the dielectric loss. The second modifier is one or more of BaTiO3 and SrTiO3, and the temperature change rate of the capacity is adjusted by using the materials with positive and negative change rates. A small amount of glass is added to form a liquid phase wrapped on the surface of the grains during the sintering process, which accelerates the migration of the material and the discharge of the gas, reduces the porosity and improves the density of the porcelain body. Finally, the dielectric constant is in the range of 50 to 60 and the dielectric loss is less than 2.5×10 -4 , capacity temperature coefficient < ±30ppm / ℃, Q*f>20000, and microwave dielectric material with C0G characteristics. The raw materials in the present invention are all domestically produced, low in cost, sufficient in quantity, and have high promotion and application value.

[0052] As a preferred implementation, the weight percentages of the components of the COG microwave dielectric material are:

[0053] 0wt%~0.7wt%MnCO3, 0wt%~0.75wt%Bi2O3, 0wt%~0.6wt%CeO2, 0wt%~3wt%SrTiO3, 0wt%~1.5wt%BaTiO3, 0wt%~0.5wt%CaO-B2O3-SiO2 glass, the balance is mainly crystalline material (1-x)BaTi4O9-xBaSm2Ti4O 12 .

[0054] As a preferred implementation, the weight percentages of the components of the COG microwave dielectric material are:

[0055] 0.1wt% MnCO3, 0.1wt% CeO2, 0.5wt% SrTiO3, 0.1wt% CaO-B2O3-SiO2 glass and the remainder of the main crystalline phase material, wherein the main crystalline phase material is 0.82BaTi4O9-0.18BaSm2Ti4O 12 Experiments have shown that under this formula, the dielectric ceramic material has the best comprehensive performance, with a higher dielectric constant, low dielectric loss and high Q*f value.

[0056] As a preferred embodiment, the composition of the CaO-B2O3-SiO2 glass is:

[0057] 38wt% ~ 45wt% CaCO3, 17wt% ~ 25wt% B2O3, 30wt% ~ 45wt% SiO2.

[0058] At the same time, the present invention also provides a method for preparing a C0G microwave dielectric material with a high dielectric constant Q value, comprising the following steps:

[0059] CaCO3, B2O3 and SiO2 are mixed according to the weight ratio, ball-milled for 5-7 hours, dried and sintered at 650±20℃ to form CaO-B2O3-SiO2 glass;

[0060] BaCO3, TiO2, Sm2O3 are used as raw materials, according to (1-x)BaTi4O9-xBaSm2Ti4O 12 The chemical formula ingredients are ball-milled for 8h to 12h, then dried, sieved, and gradually heated to 1200℃ for calcination to obtain the main sintered block material;

[0061] The main sintered block material, the first modifier, the second modifier and the CaO-B2O3-SiO2 glass are mixed in proportion, ball-milled for 20 to 26 hours, dried and sieved to obtain the porcelain material;

[0062] The ceramic material is granulated, pressed into discs, debonded, gradually heated to 1270±20° C., and sintered for 2 to 4 hours to obtain a C0G microwave dielectric material.

[0063] Among them, the grinding balls are Φ7.5 zirconium balls.

[0064] As a preferred embodiment, when preparing CaO-B2O3-SiO2 glass, alcohol is used as the medium and ball milling and mixing are performed in a ratio of material: ball: alcohol = 1:5:1.

[0065] As a preferred embodiment, when preparing the main sintered block material, water is used as the medium and ball milling is performed in a ratio of material: ball: water = 1:3:2.

[0066] As a preferred embodiment, when preparing the porcelain material, water is used as the medium and ball milling is performed in a ratio of material: ball: water = 1:5:1.2.

[0067] As a preferred embodiment, granulating the porcelain material, pressing it into discs, and removing the binder include:

[0068] The porcelain material is added with 8-9 wt% paraffin wax to form granules, which are pressed into discs using a hydraulic press, and then heated to 450°C to discharge the adhesive.

[0069] As a preferred embodiment, the heating rate is 2-4°C / min.

[0070] The technical solution of the present invention is further described in detail below in conjunction with embodiments.

[0071] It should be noted that the experimental methods used in the examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained by those skilled in the art through commercial channels.

[0072] Example 1

[0073] A method for preparing a C0G microwave dielectric material with a dielectric constant and a high Q value, comprising the following steps:

[0074] (1) The composition of CaO-B2O3-SiO2 glass is 40wt% CaCO3, 20wt% B2O3, and 40wt% SiO2. Alcohol is used as the medium and the mixture is ball-milled for 6 hours in a ratio of material: ball: alcohol = 1:5:1. After drying, the mixture is sintered at 650±20°C to form CaO-B2O3-SiO2 glass.

[0075] (2) Using BaCO3, TiO2, and Sm2O3 as raw materials, according to (1-x)BaTi4O9-xBaSm2Ti4O 12, x=0.13 chemical formula to synthesize the main crystal phase sintered block, pour the weighed raw materials into a ball mill, ball mill them in the ratio of material: ball: water = 1:3:2, the ball milling time is 8h~12h, then dry and sieve, heat to 1200℃ at a speed of 3℃ / min for calcination, to obtain the main sintered block material.

[0076] (3) The main sintered block material, the first modifier, the second modifier, and the CaO-B2O3-SiO2 glass are respectively prepared according to the formula (in g) in Table 1, and ball-milled for (20 to 26) hours at a ratio of material: ball: water = 1:5:1.2, and then dried and sieved to obtain the porcelain material.

[0077] (4) Add (8-9) wt% paraffin wax to the prepared porcelain material to granulate, use a hydraulic press to press into discs, then raise the temperature to 450°C at a rate of 2.5°C / min to discharge the binder, and then raise the temperature to (1270±20)°C at a rate of 3°C / min, sinter for 2-4 hours, and obtain the C0G microwave dielectric material.

[0078] (5) The small-formula porcelain materials in Formulations 1 to 9 and Comparative Examples 1 to 4 were subjected to a film rolling process to prepare ceramic substrate green bodies with a thickness of (0.22±0.03) mm and a length and width of 60 mm×60 mm by means of batching, film rolling and slicing. The green bodies were placed on a firing plate and placed in a box-type furnace. The temperature was raised to 900°C at a rate of 1°C / min, kept at this temperature for 2 hours for debonding, and then raised to 1250°C at a rate of 3°C / min, kept at this temperature for 3 hours for sintering to obtain ceramic substrates.

[0079] test:

[0080] 1. Wafer: Use impedance analyzer to test the dielectric constant and dielectric loss of the wafer, use high and low temperature box to test the capacitance temperature coefficient, and use insulation resistance meter and withstand voltage meter to test the insulation resistance and insulation strength of the product.

[0081] 2. Ceramic substrate: The Q*f value is tested at 5.1 GHz using a network analyzer by the open resonant cavity method. The test methods for capacitance temperature coefficient, insulation resistance and dielectric strength are the same as those for the wafer.

[0082] Comparative Example 1

[0083] The difference between this comparative example and formulation 6 in Example 1 is that the first modifier is not added.

[0084] Comparative Example 2

[0085] The difference between this comparative example and formulation 6 in Example 1 is that no second modifier is added.

[0086] Comparative Example 3

[0087] The difference between this comparative example and the formula 6 in Example 1 is that: (1-x) BaTi4O9-xBaSm2Ti4O 12 , x=0.4.

[0088] Comparative Example 4

[0089] The difference between this comparative example and the formula 6 in Example 1 is that: (1-x) BaTi4O9-xBaSm2Ti4O 12 , x=0.2.

[0090] Table 1, dielectric ceramic formula

[0091]

[0092] Each formulation in Table 1 was tested, wherein the dielectric constant, dielectric loss, insulation resistance and insulation strength, and capacitance temperature change rate were tested using a wafer, and the Q*f value was tested using a substrate. The results are shown in Table 2.

[0093] Table 2. Properties of dielectric ceramic materials of various formulations

[0094]

[0095] Figure 1 This is the SEM picture of the ceramic material of formula 6. It can be seen from the picture that the ceramic powder particles of different sizes are interspersed, and the uniformity is good, which is conducive to sintering densification after molding. Figure 2 This is the SEM picture of the porcelain body after sintering of formula 6. It can be seen from the picture that the ceramic grains are long and strip-shaped, the grains are intertwined with each other, the porcelain body has few pores and high density.

[0096] Figure 3 The XRD diagrams of the porcelain bodies of formula 1, formula 4, formula 6, and formula 9 show that the main crystal phase system of these formulas is BaTi4O9-BaSm2Ti4O 12 Composite main crystal phase.

[0097] It can be seen from Table 2 that the formulations in the embodiments have relatively high dielectric constants, low dielectric losses and high Q*f values ​​among the intermediate microwave dielectric materials, among which formulation 6 has the best comprehensive performance.

[0098] In order to further verify the compounding effect of the first modifier and the second modifier, comparative examples 1 and 2 were set up for verification. It can be seen from the data in Table 2 that compared with formula 6, comparative example 1 does not add the first modifier, and the Q*f value is reduced. Compared with formula 6, comparative example 2 does not add the second modifier, and the dielectric constant is reduced.

[0099] In order to further verify the influence of the value of x, comparative examples 3 and 4 were set up. It can be seen from the data in Table 2 that when x≥0.2 in the main crystalline phase material, the dielectric loss increases, the Q*f value decreases significantly, and is <20000 GHz, which does not meet the requirements.

[0100] Since the comprehensive performance of Formulation 6 is better, its expansion verification is carried out. The casting process is adopted, and the ceramic substrate green body with a thickness of (0.22±0.03) mm and a length and width of 60 mm×60 mm is obtained by means of batching, casting, lamination, isostatic pressing and cutting. The green body is placed on a firing plate and placed in a box furnace. The temperature is raised to 900°C at a rate of 1°C / min and kept for 2 hours for debonding. The temperature is then raised to 1250°C at a rate of 3°C / min and kept for 3 hours for sintering to obtain a ceramic substrate. At 5.1 GHz, the dielectric constant, dielectric loss and Q*f value are tested by a network analyzer using an open resonant cavity method. The other properties are consistent with the wafer test method. The results are shown in Table 3.

[0101] Table 3. Properties of dielectric ceramic substrate of formula 6

[0102]

[0103] From the data in Table 3, it can be seen that the dielectric constants of the five samples prepared by expanding the sample size of Formula 6 are all at a relatively high level, and the Q*f values ​​are relatively high.

[0104] Finally, it should be noted that the above specific embodiments are only used to explain in detail the purpose, technical solutions and beneficial effects of the present invention. It should be understood that the above description is only a specific implementation method of the present invention and is not used to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the above specific embodiments, ordinary technicians in this field should understand that it is still possible to modify the technical solutions recorded in the above embodiments, or to replace or improve some or all of the technical features therein. These modifications, equivalent replacements and improvements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and description of the present invention.

Claims

1. A C0G microwave dielectric material with a medium dielectric constant and a high Q value, characterized in that: Its composition consists of a main crystal phase material, a first modifier, a second modifier and glass; The main crystalline phase material is (1-x)BaTi4O9-xBaSm2Ti4O 12 , where 0.1≤x<0.2; The first modifier is one or more of MnCO3, Bi2O3, and CeO2; The second modifier is one or more of BaTiO3 and SrTiO3; The glass is CaO-B2O3-SiO2 glass.

2. The COG microwave dielectric material with a high dielectric constant Q value according to claim 1, characterized in that: The weight percentage of each component of the COG microwave dielectric material is: 0wt%~0.7wt%MnCO3, 0wt%~0.75wt%Bi2O3, 0wt%~0.6wt%CeO2, 0wt%~3wt%SrTiO3, 0wt%~1.5wt%BaTiO3, 0wt%~0.5wt%CaO-B2O3-SiO2 glass, the balance is mainly crystalline material (1-x)BaTi4O9-xBaSm2Ti4O 12 .

3. The COG microwave dielectric material with a high dielectric constant Q value according to claim 1, characterized in that: The weight percentage of each component of the COG microwave dielectric material is: 0.1wt% MnCO3, 0.1wt% CeO2, 0.5wt% SrTiO3, 0.1wt% CaO-B2O3-SiO2 glass and the remainder of the main crystalline phase material, wherein the main crystalline phase material is 0.82BaTi4O9-0.18BaSm2Ti4O 12 .

4. The COG microwave dielectric material with a high dielectric constant Q value according to any one of claims 1 to 3, characterized in that: The composition of the CaO-B2O3-SiO2 glass is: 38wt% ~ 45wt% CaCO3, 17wt% ~ 25wt% B2O3, 30wt% ~ 45wt% SiO2.

5. The method for preparing a COG microwave dielectric material with a high dielectric constant Q value according to any one of claims 1 to 4, characterized in that: The following steps are involved: CaCO3, B2O3 and SiO2 are mixed according to the weight ratio, ball-milled for 5-7 hours, dried and sintered at 650±20℃ to form CaO-B2O3-SiO2 glass; BaCO3, TiO2, Sm2O3 are used as raw materials, according to (1-x)BaTi4O9-xBaSm2Ti4O 12 The chemical formula ingredients are ball-milled for 8h to 12h, then dried, sieved, and gradually heated to 1200℃ for calcination to obtain the main sintered block material; The main sintered block material, the first modifier, the second modifier and the CaO-B2O3-SiO2 glass are mixed in proportion, ball-milled for 20 to 26 hours, dried and sieved to obtain the porcelain material; The ceramic material is granulated, pressed into discs, debonded, gradually heated to 1270±20° C., and sintered for 2 to 4 hours to obtain a C0G microwave dielectric material.

6. The method for preparing a COG microwave dielectric material with a medium dielectric constant and a high Q value according to claim 5, characterized in that: When preparing CaO-B2O3-SiO2 glass, alcohol is used as the medium and ball milling and mixing are performed in a ratio of material: ball: alcohol = 1:5:

1.

7. The method for preparing a COG microwave dielectric material with a medium dielectric constant and a high Q value according to claim 5, characterized in that: When preparing the main sintered block material, water is used as the medium and ball milling is performed in a ratio of material: ball: water = 1:3:

2.

8. The method for preparing a COG microwave dielectric material with a medium dielectric constant and a high Q value according to claim 5, characterized in that: When preparing porcelain materials, water is used as the medium and ball milling and mixing are performed in a ratio of material: ball: water = 1:5:1.

2.

9. The method for preparing a COG microwave dielectric material with a medium dielectric constant and a high Q value according to claim 5, characterized in that: Granulation, pressing into discs and debinding of porcelain materials include: The porcelain material is added with 8-9 wt% paraffin wax to form granules, which are pressed into discs using a hydraulic press, and then heated to 450°C to discharge the adhesive.

10. The method for preparing a COG microwave dielectric material with a medium dielectric constant and a high Q value according to claim 5, characterized in that: The heating rate is 2-4℃ / min.

Citation Information

Patent Citations

  • Two-phase compound microwave medium ceramic material and preparation method thereof

    CN102757219A

  • Microwave dielectric ceramic material and preparation method

    CN111153694A

  • High frequency dielectric ceramic composition and its dielectric devices

    CN1303106A